2008
DOI: 10.1111/j.1469-7998.2008.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of group size among African buffalo herds in a forest‐savanna mosaic landscape

Abstract: Documenting within species group size variation is important to completely understand social organization within species and to interpret variation among species. Here, I investigated group size of African buffalo Syncerus caffer over 2 years in a heterogeneous landscape. African buffalo use closed continuous forest and vast open savannas, and anecdotal observations suggest that habitat type influences their social structure. While the Cape buffalo Syncerus caffer caffer is well studied, few data exist for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…Sexual segregation has also been observed in other ungulates (e.g., bighorn sheep; Ruckstuhl 1998;Ruckstuhl and Neuhaus 2000;Ruckstuhl and Kokko 2002). On the contrary, as evidenced in previous studies (Melletti et al 2007a, b;Korte 2008bKorte , 2009 forest buffalo herds live in quite stable groups and members are mainly permanent part of it. In this 2 years study the male was always observed inside the herd.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Sexual segregation has also been observed in other ungulates (e.g., bighorn sheep; Ruckstuhl 1998;Ruckstuhl and Neuhaus 2000;Ruckstuhl and Kokko 2002). On the contrary, as evidenced in previous studies (Melletti et al 2007a, b;Korte 2008bKorte , 2009 forest buffalo herds live in quite stable groups and members are mainly permanent part of it. In this 2 years study the male was always observed inside the herd.…”
Section: Discussionmentioning
confidence: 77%
“…Studies of various species have shown that under conditions of increasing predation risk, animals form larger and denser groups (Spieler 2003;Hoare et al 2004). Korte (2008b) found unusually high number of observations of old buffaloes and this suggests probably low predation pressure on adult while food resources probably influenced group size more than predation. Moreover, there is some evidence that feeding competition can simultaneously have a dilution effect, increasing the overall distance among individuals within a group to decrease foraging interference (Wrona and Jamienson 1991;Parrish and Hamner 1997;Krause and Ruxton 2002).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly, in the lowland forests of Congo and the mixed forest-savanna of Gabon, both areas expected to be predator free (Bauer et al 2003), buffalo herds average fewer than 50 individuals (Sinclair 1977, Korte 2008. The majority of the abovementioned populations were estimated to be a similar size to the current population in Main Camp, so population size effects cannot explain the differences observed currently …”
Section: Discussionmentioning
confidence: 99%